An Analysis of Students’ Collocation Translation in EFL Classroom - Febriana, Indri; Maisarah, Ira (International Journal of Language Pedagogy, 2021)
This study sought to answer the question, "What is the English collocation found in student descriptive text translation?" This study was designed as descriptive qualitative research, and the study's data was described qualitatively. The data was taken from the student’s descriptive translation. The sources of the data in this study were sentences and expressions that contain collocation. Documentation is the only instrument used in collecting the data. To analyze the data, the researchers used data reduction, data display, and conclusion drawing/verification. The result of this study showed that (1) there were sixteen collocations found in student’s descriptive text translation and (2) the meanings of English collocations were fourteen had denotative meaning. To conclude, the collocation words do not only have one meaning but also have many meanings, and change the meaning based on the structure of the sentence in the text.